Θεία Παιδαγωγία. Παιδαγωγικά στοιχεία στο Μεγάλο Κανόνα του Ανδρέα Κρήτης (εκδ. Ακρίτας, 2000)
This research comes to illuminate a masterpiece of ecclesiastical poetry, the Great Canon of Saint Andrew of Crete (660 - 740 A.D.), with the light of two scientific fields: Theology and Pedagogy. It comes to fill the gap of a special treatise on the pedagogic elements and hermeneutical analysis of the Great Canon, on which few and restricted essays have been written, mostly of hymnologic interest.      A hymnological approach of the poem (life and personality of the writer, writing circumstances, language and style) was the first step of the survey. The Great Canon is of tremendous literary value. The poetic and dense language adjusted to a pre-determined poetic measure is a most fascinating instrument, used ingeniously by the composer, whose sacred life was even more fascinating. Apart from the pedagogic character of the Canon, its presence in the Great Lent’s typikon satisfies the aesthetic need of a descend pray. As a liturgical poem, the Great Canon abounds with Orthodoxy. Partially examined, its dogmatic elements concern all branches of systematic Theology. Its full alignment with Orthodoxy discloses the potentials of its pedagogic purpose, which is repentance. Liturgical pedagogy is quite a useful term to describe the procedure of learning how to feel and follow God’s Will through Worship. This pedagogy is not something beyond or alien to any other pedagogic system. Repetition, familiarization, “material participation” (actual physical presence) to Worship are conditions sine qua non for any kind of educational attempt, even if the pedagogic aim has less to do with expanding cognitive faculty and more with enriching people’ s hearts with authentic feelings. Andrew of Crete is overwhelmed with awe and every single word of his Canon is the result of a sincere feeling. Therefore, he can and does «teach» and convey awe to the others. Saint Andrew was and still is an active member of the Church. His life proves that a composer’ s sanctity can bear dogmatic accuracy in his words, renovating inspiration in the difficult task of waking up people’s consciences that belong in different ages, educational levels and spiritual condition. Nevertheless, his pilgrimage has a common basis to stand up: Their membership to the Church, their conscientious and freewill participation in liturgical life, and their intention to follow up the spirit of the Great Lent. The Great Canon is the most intense assault to human egoism that ecclesiastical poetry can give. This impetuous self - assault in its full extent happens only once a year during the Great Lent. This is the most one can bear.  The Greek term metania for repentance means change of mind. The composer addresses to the innermost recesses of people’ s hearts so as to instill the procedure of metania in a most discreet way. He leads people to personal conclusions about their own spiritual condition revealing that the only reason to mourn is the loss of Paradise. The conclusions are derived spontaneously as the Sacred Story is unfolded in a profoundly dramatic way. Divine Incarnation brings to the world the possibility of a real relationship with God, which is the basis of the orthodox concept of Pedagogy. In this relationship the unexpected and unstable party is man, not Cod. God is Love and there is nothing more reliable and invariable than love. Man’s personal controversies on the one hand, and the simplicity of the evangelic word on the other, compress any rational pre-scheduled pedagogic action; the only strong argument for the possibility of one’s repentance is the “improvisation” of Paraclete.  The classic pedagogic principles are present in the Great Canon and get related to its ceremonial use, orthodox spirituality and mystical catechesis. They are orientated to ecclesiastical life. An effort to reveal the sequence of the writer’s teaching process has led to the safe conclusion that he follows a series of paradigms, parables and pictures derived from the Bible. Moreover, there is enough space for a personal view on the text, and this is why an original hermeneutic approach, yet in complete accordance with Orthodox Pedagogy, was attempted. Common pedagogic means, such as addiction, encouragement, reinforce-ment, advice, orders, paradigms and models are present in the Canon, though not always visible at first glance. Their presentation and analysis was an indispensable, yet profoundly demanding, part of the research. For instance, a pedagogue might be surprised to hear that lamentation serves encouragement. A theologian, however, can easily understand why the Canon’ s mourning is not rendered as the tragic woe of ancient Greek fatality but as the «hopeful despair» of patristic language. Certainly, in this survey Theology is not an opponent to Pedagogy. Each science has been a useful servant to the other. Both of them are something more than scientific fields. They deal with the deepest needs of the human soul - the desire to reach beauty, wisdom and happiness. Both of them have questions to pose and answers to give. However, time has come for the scientific field of Pedagogy to give a sincere answer to the crucial question of God’ s existence, because if He exists he cannot be ignored as a Teacher. URL: https://www.didaktorika.gr/eadd/handle/10442/12018